Design and construction criteria for domes in low-cost housing - Talocchino, Gianfranco (My University, 2007)
This dissertation investigates the different design and construction considerations involved when building a masonry dome. A detailed shape investigation was undertaken in order to summarize the best shaped dome structures. General recommendations are given for the shapes that produce the least tension and the most useable space. The effects of openings, temperature loading and wind loading were considered and a finite element analysis of the final structure was undertaken. It was found that regions of high tension exist around openings, especially under temperature loading, and materials suitable to resisting this tension were investigated (fibre plaster, chicken wire mesh and wire wrapping around openings). The final structure was built using an inflatable formwork. The construction procedure was well documented and a study of alternative methods of construction is presented. This dissertation shows that a durable, architecturally and structurally efficient low-cost masonry dome can be built if proper attention is given to minimizing and resisting tension within the structure.
Student Number : 0003370N - MSc dissertation - School of Civil and Environmental Engineering - Faculty of Engineering
Keywords: domes; design; construction; low-cost